2010
DOI: 10.1128/jvi.02028-09
|View full text |Cite
|
Sign up to set email alerts
|

Extralymphoid CD8 + T Cells Resident in Tissue from Simian Immunodeficiency Virus SIVmac239Δnef-Vaccinated Macaques Suppress SIVmac239 Replication Ex Vivo

Abstract: Live-attenuated vaccination with simian immunodeficiency virus (SIV) SIVmac239⌬nef is the most successful vaccine product tested to date in macaques. However, the mechanisms that explain the efficacy of this vaccine remain largely unknown. We utilized an ex vivo viral suppression assay to assess the quality of the immune response in SIVmac239⌬nef-immunized animals. Using major histocompatibility complex-matched Mauritian cynomolgus macaques, we did not detect SIV-specific functional immune responses in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 55 publications
4
26
0
Order By: Relevance
“…Responses in BAL fluid samples were more robust than those in the blood samples (Fig. 1B and Table S1), consistent with earlier studies of SIV-specific CD8 ϩ T cell responses at this mucosal site (17).…”
supporting
confidence: 80%
“…Responses in BAL fluid samples were more robust than those in the blood samples (Fig. 1B and Table S1), consistent with earlier studies of SIV-specific CD8 ϩ T cell responses at this mucosal site (17).…”
supporting
confidence: 80%
“…CD8 ϩ T lymphocytes have been shown to be critical for the control of HIV-1 infection in persons with very low levels of plasma HIV-1 RNA in the absence of antiviral therapy (7,10,15,22,25). A similar observation has also been made in SIV-infected rhesus monkeys (8,9,12,14). For example, Hansen et al demonstrated in nonhuman primates that peak SIV-specific CD8 ϩ T lymphocyte responses following immunization were associated with virologic control in rhesus monkeys immunized with rhesus cytomegalovirus vaccines that included Gag antigens (9).…”
Section: Discussionsupporting
confidence: 58%
“…A wealth of literature has shown that CD8 ϩ T lymphocytes can mediate control of viremia in HIV-1-infected humans (2,7,10,11,22,25) and SIV-infected rhesus monkeys (8,9,23) and that T lymphocytes specific for HIV-1 Gag epitopes are associated with virologic control in vivo (4,5,13,15,26,28). Vaccine trials in nonhuman primates have also indicated an association between Gag-specific cellular immune responses and virologic control in vaccinated rhesus monkeys following SIV challenge (1,12,14,18,27).…”
mentioning
confidence: 99%
“…[8][9][10] Several studies have indicated that CD8 C T lymphocytes can control viremia in HIV-1 infected humans [11][12][13][14] and SIV infected monkeys. 11,[15][16][17][18] It has also been shown that CD8…”
Section: Introductionmentioning
confidence: 99%